2004
DOI: 10.1189/jlb.0804473
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 supports the generation of a dendritic cell subset from murine bone marrow with altered endocytosis capacity

Abstract: Dendritic cells (DC) of myeloid origin can be generated from mouse bone marrow (BM) using granulocyte macrophage-colony stimulating factor (GM-CSF). Immature major histocompatibility complex (MHC) II(low) DC are known to bear a high endocytosis capacity, in contrast to DC precursors and mature DC. Now we found that a subset of MHC II(low) DC in BM-DC cultures is unable to exert mannose receptor-mediated endocytosis of fluorescein isothiocyanate (FITC)-dextran (DX) and resembles immature Langerhans cells (LC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 39 publications
1
39
2
Order By: Relevance
“…It has been demonstrated that antigen uptake and processing correlates with the maturation status of DCs. 41,42 Our data suggest that C5aR activation during GM-CSF-mediated DC differentiation is an important signal that keeps DCs in a more immature state required for antigen sensing. We were not able to assign the decreased potency of antigen uptake to a particular endocytosis pathway.…”
Section: Discussionmentioning
confidence: 96%
“…It has been demonstrated that antigen uptake and processing correlates with the maturation status of DCs. 41,42 Our data suggest that C5aR activation during GM-CSF-mediated DC differentiation is an important signal that keeps DCs in a more immature state required for antigen sensing. We were not able to assign the decreased potency of antigen uptake to a particular endocytosis pathway.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, the CD11b Ϫ/ϩ Ly6C/G Ϫ c-Fms Ϫ population remained DC under all conditions and exhibited features of LC, with expression of E-cadherin and CD205; these DC were less capable of internalizing DexFITC and displayed greater levels of MHCII and allostimulatory capability. A second study extended these observations and divided immature MHCII int BM DC into two groups based on the ability to internalize DexFITC (27). DexFITC ϩ DC were CD11b high Ly6C/G high E-cadherin Ϫ , whereas DexFITC Ϫ DC were CD11b int Ly6C/G Ϫ E-cadherin ϩ .…”
Section: Discussionmentioning
confidence: 99%
“…The precise developmental relationship between the CD11b high Ly6C ϩ and CD11b int Ly6C Ϫ DC populations that differentiate in GM-CSF-supported BM cultures remains unclear, although the above-mentioned studies suggest that the CD11b int DC may arise via multiple pathways (27,28). We do not yet have strong evidence that one DC population arises from the other, or that the two DC populations arise from distinct undifferentiated myeloid progenitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For one, the variability of BM-DCs generated via different protocols has already lead to substantial debate on an immunological level. For instance, Lutz et al observed major differences in the immune stimulating properties of BM-DCs based on the serum and cytokine cocktails used during their differentiation from bone marrow cells [19,20].…”
Section: Introductionmentioning
confidence: 99%